UJI BAKTERERIOLOGIS DAGING AYAM BOILER (Gallus gallus domestica) YANG DI JUAL DIPASAR MODERN KOTA PADANG - Mulya, Diga; Fifendy, Mades; Fitriani, Vivi (STKIP PGRI Sumbar, 2014)
ABSTRACT When the current food safety issues very interesting people . Almost all food stuffs contaminated with bacteria and is still far in terms of cleanliness . One food that is contaminated chicken meat boiler . Chicken meat is a food of high nutritional value because it is rich in protein , fat , minerals and other substances that the human body needs . This study aims to conduct bacteriological tests on the boiler chicken ( Gallus gallus domestica ) of the modern market in the city of Padang . Descriptive research method . The study was conducted from September 2013 to January 2014 in the Laboratory Kopertis X West Sumatra . Sampling was done randomly at 3 modern market in the city of Padang , namely Robinson Plaza Andalas , Hypertmart Basko Grand Mall and Brothers Mini Market . Further testing in total plate count test and the numbers test Escherika coli . From the research results obtained chicken meat contains boiler plate count bacteria in the range of 28 x 10-6 to 0 x 10-6 per cfu / g sample . Plate count bacteria Escherichia coli with a range of 20 x 10-1 to 56 x 10-1 per cfu / g sample . The conclude that boiler chicken meat sold in the market town of Padang modern E.coli bacteria contaminated in excess of the maximum li mit of SNI and advised the public to be careful eating chicken boiler .